Formation of the Nature Protection Experience of Junior Pupils of the Netherlands - Olena Derkach (Pedagogical Discourse, 2013)
The article provides the results of the observations of the formation of nature protection experience of junior pupils in the Netherlands. The comparative analysis of ecological teaching and education of Dutch and Ukrainian children aiming to attract positive experience, to acquaint with the new approaches and their use in the development and mastering of domestic methods is made. Ecologization of school books of primary school of the Netherlands is analyzed. Peculiarities of conducting educational excursion in the open air and research activity of junior pupils in the zoological gardens of the country are studied. Parents’ influence onto the formation of nature protective experience of children and the public role in this process are reflected.